Outcomes after acute intracerebral haemorrhage - Krishnan, Kailash (2017)
Primary Intracerebral haemorrhage is a severe form of stroke with poor prognosis attributed to haematoma characteristics. High blood pressure is present during the acute phase of intracerebral haemorrhage and associated with poor outcome in part through expansion of haematoma.